ANALISIS HOTS DALAM PEMECAHAN MASALAH DITINJAU DARI KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Nisvu Nanda Saputra; Ismatul Maula; Siska Indriyani; Tiyur Maharani (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
The purpose of this study is to analyze the ability of students to solve problems in HOTS problems in terms of the ability to thinkcreatively. The approach used in this study is a qualitative approach. The research subjects were 6 grade VIII students of SMP Negeri1 Legok, Tangerang Regency. Data collection techniques in the form of observation, tests and interviews. The results showed that theability of high-level creative thinking can solve HOTS type questions correctly and in detail in each answer, and students of mediumlevelcreative thinking can complete several stages of HOTS type problems but the students' work is not detailed in each answer, whereasstudents Low-level creative thinking skills can solve HOTS type problems, but the solution is wrong and every answer is wrong. Overallfor low ability students still need coaching.